PEMBANGUNAN GAME LOST CHAIN MENGGUNAKAN BLOCKCHAIN DAN GASLESS TRANSACTION - Fajar Darmawan; Bakhtiar Bakhtiar (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2023)
Blockchain technology has emerged as a disruptive innovation, opening the way for the creation of decentralized apps (dApps). However, the current implementation of blockchain technology requires gas fees, which are transaction fees paid to miners for transaction validation. Gas fees restrict the adoption of decentralized applications because users must pay these fees to interact with the network. The method to reduce consumer burden by utilizing transactions without gas is using meta-transactions. Meta-transactions allow third parties to pay fees on behalf of users, so users don't have to pay expensive gas fees. These solutions have the ability to simplify the user experience, reduce end-user cognitive load, and increase dApp adoption. The results of this study indicate that gasless transactions are a promising method for relieving user tension and increasing dApp adoption. Overall, this research offers useful insights into the problem of gas costs in blockchain technology and suggests practical solutions to improve user experience.